Genomewide association analysis of warfarin dose requirements in Middle Eastern and North African populations - Nihal El Rouby; Mohamed H. Shahin; Loulia Bader; Sherief I. Khalifa; Hazem Elewa (Wiley, 2022)
Abstract To date, there has been no genomewide association study (GWAS) from the Middle East and North African (MENA) region to identify genetic variants associated with warfarin dose variability using this approach. In this study, we aimed to conduct the first GWAS of warfarin dose requirements in patients from the MENA region. A total of 132 Qatari (discovery) and 50 Egyptians (replication) were genotyped using Illumina Multi‐Ethnic Global BeadChip Array. A GWAS was performed on log‐transformed weekly warfarin dose in the studied population, adjusting for clinical characteristics and ancestry. The genomewide signals from the discovery cohort were tested in the Egyptian cohort. A GWAS meta‐analysis, including the Qatari and Egyptian cohorts, was also performed and the output from this analysis was used in a gene‐based analysis. The discovery analysis in Qatari identified five genomewide single‐nucleotide polymorphisms (SNPs) in chromosome 16. These signals were replicated in the Egyptian cohort. Combining the two data through a GWAS meta‐analysis strengthened the association in chromosome 16 with VKORC1 rs9934438 being the lead genomewide signal (β = −0.17, 6 × 10−15). Other SNPs were identified in chromosome 10 at a p value less than 1 × 10−5. The genetic variants within VKORC1 rs9934438 and CYP2C9 rs4086116 explained 39% and 27% of the variability in the weekly warfarin dose requirement in the Qatari and Egyptians, respectively. This is the first GWAS of warfarin dose variability in the MENA region. It confirms the importance of VKORC1 and CYP2C9 variants in warfarin dose variability among patients from the MENA region.